2023
DOI: 10.1101/2023.01.27.525929
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing the impact of successive soil cultivation onMeloidogyne enterolobiiinfection and on soil bacterial assemblages

Abstract: Soil cultivation may change the soil microbiome and alter interactions between plants and parasites. The objective of this work was to evaluate temporal changes in plant health, microbiome abundance, bacterial diversity and the plant-parasitic nematode, Meloidogyne enterolobii incidence in two soil fields with different agricultural uses. Soil samples were collected from a commercial tomato production field (agricultural soil) and a single-cultivation strawberry field (native soil). Samples for the second expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…These findings indicate that the efficacy of collagen and chitin in reducing nematode populations may vary depending on soil type, and therefore different soil microbiome, suggesting the indirect effect of the amendments in controlling the plant-parasitic nematode. Prior research has suggested that alterations in soil cultivation practices can impact soil suppressiveness and alter the microbial community to favor defense against M. enterolobii (Pasche et al, 2023). Thus, the soil microbes present in different soil types may differ in their use of collagen and chitin, impacting their efficacy against M. enterolobii infection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These findings indicate that the efficacy of collagen and chitin in reducing nematode populations may vary depending on soil type, and therefore different soil microbiome, suggesting the indirect effect of the amendments in controlling the plant-parasitic nematode. Prior research has suggested that alterations in soil cultivation practices can impact soil suppressiveness and alter the microbial community to favor defense against M. enterolobii (Pasche et al, 2023). Thus, the soil microbes present in different soil types may differ in their use of collagen and chitin, impacting their efficacy against M. enterolobii infection.…”
Section: Discussionmentioning
confidence: 99%
“…In standard inoculation conditions, the native soil exhibited reduced metabolic activity. This difference may be due to the soil having a lower baseline metabolic activity due to inherent limitations in nutrient availability or microbial diversity due to less anthropogenic influence (Pasche et al, 2023). However, under high inoculum pressure, native soil demonstrated a notable increase in metabolic activity, suggesting a possible adaptive response to stress that aligns its metabolic profile more closely with that of agricultural soil.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The impact of soil and rhizosphere microbiome on soil‐borne diseases in plants is well‐established (Lee et al, 2021; Pasche et al, 2023), demonstrating the significant role of below‐ground microbial communities in plant health and disease resistance. However, our understanding of how these soil–root microbiome dynamics influence above‐ground diseases, particularly foliar diseases, is still underexplored (Trivedi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%